TINJAUAN PERAN CUSTOMER SERVICE DALAM PENGELOLAAN PASIEN KONTROL PERTAMA PASCA RAWAT INAP DI RSU KUMALA SIWI MIJEN KUDUS - Ariyani, Desi Dwi; I Sudra, Rano (Poltekkes Kemenkes Malang, 2025)
Abstract: Hospitals as health service providers play a crucial role in providing the comprehensive services not only in the medical area but also in the non-medical aspects such as information services, administration, and patient's comfort. One of the important factors that support the achievement of optimal service is the role of Customer Service Officer (CSO). The purpose of this study was to understand the role of Customer Service in managing the first post-hospitalization control patients at RSU Kumala Siwi Mijen Kudus. The research method used qualitative description. Data collection used an interview method with 7 respondents. The study results showed that the role of customer service in managing the first post-hospitalization control patients at RSU Kumala Siwi Mijen Kudus was not optimal, in connection with the ongoing complaints regarding the waiting time for service. In conclusion, the implementation of CSO duties at RSU Kumala Siwi Mijen Kudus is generally run by the policies and SOPs that have been set. Keywords: Customer Service Officer, Patient, RSU Kumala Siwi